A threefold perspective on the role of a pockmark in benthic faunal communities and biodiversity patterns. (January 2021) - Sánchez, Nuria; Zeppilli, Daniela; Baldrighi, Elisa; Vanreusel, Ann; Lahitsiresy, Max Gasimandova; Brandily, Christophe; Pastor, Lucie; Macheriotou, Lara; García-Gómez, Guillermo; Dupré, Stéphanie; Olu, Karine
Abstract: Pockmarks are circular-shaped depressions that increase seabed heterogeneity and are characterized by discontinuous fluid emissions. To understand how environmental conditions of pockmarks affect the structure of macro- and meiofauna, we investigated two sites in a pockmark field in the northwestern Madagascar margin. In a comparative approach, we explored the community structure of the dominant taxa (Polychaeta, Nematoda and hyaline foraminifera) in each component (macro-, metazoan meiofauna and foraminifera, respectively). The investigated active pockmark showed approximately two times higher meiofauna abundance compared to in a site away from another pockmark field, but macrofauna showed the opposite trend, with almost half density at the pockmark site. However, at both sites, macro- and meiofauna showed higher richness and abundance values in the top well-oxygenated layers of the sediment than in the underlaying ones. Polychaeta and Nematoda showed lower richness in the pockmark, opposed to hyaline foraminiferans, but lower evenness in the pockmark was found for the three groups. The detection of gas flares in the water column attests of the recent activity within the pockmark. High amount of sulfur-bearing minerals (mainly pyrite) evidences a production of dissolved free sulfides (not detected at the time of sampling) by sulfate reduction process driven by organic matter degradation and anaerobic oxidation of methane. Furthermore, recent increase in sedimentation rates in the past 70 years and organic matter inputs could have led to higher organic matter degradation rates resulting in reduced conditions and a high oxygen consumption. All this together seem to act as key factors in the determination of variation in richness, abundance and community composition of macrofauna and meiofauna. Additionally, some taxa seem to be more tolerant to these extreme conditions, such as species belonging to the Nematoda genus Desmodora and the phylum Kinorhyncha, which are highly abundant in the pockmark, and hence, may be considered as potential bioindicators of pockmark activity in this area. Further studies are required for a better assessment. Highlights: Environmental conditions of pockmarks affect benthic community composition. Meiofaunal taxa are able to take advantage of pockmark activity, i.g Desmodora . Desmodora nematode could be a benthic indicator of fluid emission. Benthic community compositions are largely dissimilar between the two sites.